Identification, Expression Profiling, Microbial Binding, and Agglutination Analyses of Two Cathepsin B Genes in Black Rockfish (Sebastes schlegelii) - Xinghua Zhuang; Xingchun Li; Wenpeng Li; Xuan Xu; Fengjun Lin; Yiying Liu; Chonghui Chen; Xiaoxu Zhang; Pei Zhang; Chao Li; Qiang Fu (Marine Drugs)
As a lysosomal cysteine protease of the papain subfamily, cathepsin B (CTSB) is characterized by its innate immune functions and hydrolytic activity. However, the functions of CTSB in the immune responses of teleosts remain to be clarified. In this study, two CTSB genes in S. schlegelii, SsCTSBa and SsCTSBb, were identified. Both SsCTSBa and SsCTSBb are composed of a 993 bp ORF encoding 330 amino acids. It was found in a phylogeny analysis that both genes form monophyletic clades with their orthologous counterparts of Honeycomb rockfish (Sebastes umbrosus). A synteny analysis indicated that the CTSB homologues were comparatively conserved during vertebrate evolution. Additionally, quantitative real-time PCR revealed the ubiquitous mRNA expression of SsCTSBa and SsCTSBb in all of the examined tissues, and substantially differential expression patterns could be observed following Aeromonas salmonicida infection. A subcellular localization analysis demonstrated that the distribution of SsCTSBa and SsCTSBb was mainly in the cytoplasm. Moreover, rSsCTSBa and rSsCTSBb showed strong binding to Poly(I:C) and exhibited diverse agglutination effects on different bacteria. Overall, these findings suggest that the CTSB genes in black rockfish might show essential functions in the host defense of teleosts against bacterial infections, providing valuable insights for further investigations into the immune mechanism of teleost CTSB.